2017
DOI: 10.1016/j.adro.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation with an IMRT technique in 15 to 28 fractions is better tolerated than standard doses of 3DCRT for LAPC

Abstract: PurposeTo review acute and late toxicities after chemoradiation for locally advanced pancreatic ductal adenocarcinoma in patients who were treated with escalated dose radiation (EDR).Methods and materialsMaximum Common Terminology Criteria for Adverse Events Version 4.0 acute toxicities (AT) during radiation and within 60 days after radiation were recorded for both acute gastrointestinal toxicity and overall toxicity (OT). Late toxicities were also recorded. EDR was generally delivered with daily image guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…This is consistent with other studies which demonstrated that IMRT use spares normal tissue and is associated with lower GI toxicities in upper abdominal malignancies. [29][30][31][32] The use of IMRT technique did not compromise local control. Tumor size and distance from nearest GI mucosa were not taken into consideration while analyzing the protective role of IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies which demonstrated that IMRT use spares normal tissue and is associated with lower GI toxicities in upper abdominal malignancies. [29][30][31][32] The use of IMRT technique did not compromise local control. Tumor size and distance from nearest GI mucosa were not taken into consideration while analyzing the protective role of IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LAP-07 trial 3 failed to show an overall survival benefit to radiation at standard doses, it did show benefits in terms of local control and time off of chemotherapy. At higher radiation doses, however, our institutional data suggests improved overall survival (17.8 months vs 15 months) 4 and recurrence-free survival (10.2 months vs 6.2 months), in addition to decreased acute grade 3+ gastrointestinal toxicity (1% vs 14%) 5 even at higher doses (BED>70Gy) with advanced radiation delivery techniques including use of 4-dimensional computed tomography, breath-hold technique, and image-guided radiation therapy.…”
Section: Introductionmentioning
confidence: 76%
“…Only 1 out of 200 patients in the cohort developed Grade 3 acute toxicity. In a follow-up comparative study of treatment-related toxicities in patients who had a dose escalated regimen (biological equivalent dose >70 Gy) using IMRT and those who had standard radiation dose of 50.4 Gy in 28 fractions delivered using 3D-CRT, the group observed an overall lower rates of Grade 3 acute in those who received dose-escalated regimen delivered using IMRT compared those who received standard radiation dose delivered using 3D-CRT technique (4% vs. 16%, P=0.004) (21). Six of 59 patients who received the dose-escalated regimen developed Grade 3+ late toxicity in form of either gastrointestinal stricture or bleeding.…”
Section: Intensity Modulated Radiation Therapy (Imrt) For Lapc (Table 3)mentioning
confidence: 97%
“…A retrospective study by Colbert et al . (21) showed that patients who had IMRT to a higher dose (escalated dose fractionation) had lower rates of Grade 3+ acute toxicities during radiotherapy, compared to those who had 3D-CRT with conventional dose fractionation of 50.4 Gy in 28 fractions.…”
Section: Intensity Modulated Radiation Therapy (Imrt) For Lapc (Table 3)mentioning
confidence: 99%